The Influence of Learning Video Media on Students' Interests and Critical Thinking Skills in Social Studies Learning for Class VIII SMPN 2 Bantan - Eva Kurnia Ningsih; Musnar Indra Daulay; Imam Hanafi (ASIAN: Indonesian Journal of Learning Development and Innovation, 2024)
This study aims to determine the effect of learning video media on students' interest and critical thinking skills in social studies learning in class VIII of SMPN 2 Bantan. This study uses a quantitative approach with a quasi-experimental design. The research sample consisted of 62 students divided into experimental and control classes. The instruments used in this study were a learning interest questionnaire and a critical thinking ability test. The results showed that there was a significant effect of the use of learning video media on students' learning interest and critical thinking skills. In the experimental class, the average pretest value of learning interest was 10.52 and increased to 17.32 in the posttest, while the control class increased from 11.55 in the pretest to 15.52 in the posttest. Students' critical thinking skills in the experimental class increased from an average value of 61.90 in the pretest to 85.58 in the posttest, while in the control class increased from 63.39 in the pretest to 66.23 in the posttest. Data analysis using normality tests, homogeneity tests, and t-tests showed that the data were normally distributed and homogeneous. Independent sample t-test showed significant differences between the experimental and control classes in the posttest, both for learning interest and critical thinking skills (p < 0.05). This study concluded that learning video media is effective in increasing students' interest and critical thinking skills in social studies learning. Therefore, it is recommended for teachers to utilize learning video media as one of the strategies in improving the quality of social studies learning.